2013
DOI: 10.1161/strokeaha.113.002014
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Decompression for Space-Occupying Cerebral Infarction

Abstract: A pooled analysis of 3 European randomized trials has shown that in patients with space-occupying hemispheric infarction, surgical decompression initiated within 48 hours of stroke onset strongly reduces the risk of death and increases the chance of a favorable functional outcome at 1 year. However, this large reduction in case fatality comes at the expense of an increased risk of moderately severe or severe disability at 1 year, 1 and the majority of survivors have global cognitive impairment.2 Some authors h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
62
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(64 citation statements)
references
References 7 publications
(10 reference statements)
1
62
0
1
Order By: Relevance
“…Several randomized controlled trials (RCTs) have demonstrated that DC can reduce the ICP and reduce mortality to 17% to 36%. [2][3][4][5][6][7] Although DC is a lifesaving treatment, not all patients with MCHI can receive the surgery quickly enough. Additionally, patients who routinely take antiplatelet or anticoagulant drugs are at an increased risk of developing massive bleeding during or after DC, which limits its application.…”
mentioning
confidence: 99%
“…Several randomized controlled trials (RCTs) have demonstrated that DC can reduce the ICP and reduce mortality to 17% to 36%. [2][3][4][5][6][7] Although DC is a lifesaving treatment, not all patients with MCHI can receive the surgery quickly enough. Additionally, patients who routinely take antiplatelet or anticoagulant drugs are at an increased risk of developing massive bleeding during or after DC, which limits its application.…”
mentioning
confidence: 99%
“…1). Fourteen of them were finally included to the meta-analysis, including eight RCT [14][15][16][17][18][19][20][21] and six retrospective cohort studies [22][23][24][25][26][27]. The 423 DC cases and 389 conservative managed cases were involved.…”
Section: Search Results: An Assessment Of Risk Of Biasmentioning
confidence: 99%
“…Although existing data support the use of 12-month functional outcomes rather than earlier time points, it is recognized that some patients continue to regain function after 1 year, which could lead to an underestimation of treatment effect. 27,36 Only one RCT of DC has reported outcomes past 12 months. 27 …”
Section: Discussionmentioning
confidence: 99%
“…Hofmeijer et al 5 reported a post hoc analysis of 39 patients enrolled in HAMLET within 48 hours of stroke onset, but did not report baseline patient characteristics or whether their initial randomization stratification was maintained in this subgroup. 5,27 Secondary to these concerns, Slezins et al 23 and Hofmeijer et al 5 both received an unclear risk of bias rating. A full risk of bias rating table is included in figure e-1.…”
Section: Risk Of Bias For Independent Studiesmentioning
confidence: 99%